In Search of Predatory Pricing - Isaac, R. Mark; Smith, Vernon L. (Journal of Political Economy, 1985)
Focuses on the reproduction of predatory pricing in laboratory environment. Definition on predatory pricing; Methods used to construct experimental design; Effect of predation on price increase and efficiency. Focuses on the reproduction of predatorypricing in laboratory environment. Definition on predatorypricing; Methods used to construct experimental design; Effect of predation on price increase and efficiency.